2017
DOI: 10.1177/0969733017718393
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Student Attitudes toward Euthanasia: A Cross-Sectional Study

Abstract: It is recommended to explore the factors that induced nursing students' tendency to euthanasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 20 publications
0
37
1
Order By: Relevance
“…Also this study also showed there are a number of misconceptions among Iranian Muslim nursing students about the definition of euthanasia. However, most students show a positive attitude toward euthanasia in accordance with their clinical experience [41].…”
Section: Discussionmentioning
confidence: 75%
“…Also this study also showed there are a number of misconceptions among Iranian Muslim nursing students about the definition of euthanasia. However, most students show a positive attitude toward euthanasia in accordance with their clinical experience [41].…”
Section: Discussionmentioning
confidence: 75%
“…In this study, the majority of secular students supported PAD, while those who identified as religious were predominantly opposed to it. Similarly, a study of Muslim nursing students in Iran found 64% were in strong opposition to active euthanasia (defined as care providers "taking active steps to terminate the patient's life") and the majority of the respondents agreed that their religious affiliation was a strong influence in their attitude (Hosseinzadeh & Rafiei, 2017). Notwithstanding the diverse cultural considerations of these studies, what differed in the current Canadian study was an overriding support for MAiD from all students, even where tensions and ambiguity arose on the basis of religious beliefs.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…To overcome these limitations, a secondary search strategy was performed as follows. The references listed in the 46 selected articles 1,3,5,6,[8][9][10][11][12][13][15][16][17][20][21][22][23][24][25][26]29,30,32,33,36,[40][41][42][43][44]46,[48][49][50][51][52][53][54][55][56][57]59,66,[71][72][73] were checked for further relevant references, and religious books (Quran and hadith) and legal codes of selected countries were also consulted from websites. The secondary search strategy resulted in an additional 30 references, which we included in this review.…”
Section: Methods For Literature Searchmentioning
confidence: 99%